(untitled) (Hekima Review, 2009)
Although female genital mutilation has been outlawed in Kenya and opposed by civil society as an abuse of the right and human dignity of girls and young women, yet the practice continues unabated, albeit secretly in some parts of Kenya. Through a contextual exposition of the intricacies of female circumcision as practiced in Kenya and also in some other parts of Africa, the paper closely analyzes its medical ethical implications as well as proposes some interventions that can be meaningful in understanding and addressing the negative aspects of the practice today while retaining its inherently positive values.